The Effect of Glutaraldehyde Crosslinking on the Morphology of PVA/Chitosan/Collagen Composite Nanofibers - Yuliani, Ria; Sukma Pranastia, Dewa Ayu; Rupiasih, Ni Nyoman; Supardi, I Wayan; Suarbawa, K N (BULETIN FISIKA; Vol 25 No 1 (2024): BULETIN FISIKA February EditionDO - 10.24843/BF.2024.V25.i01.p08, 2024)
One technique to increase the stability of PVA/chitosan/collagen (PChK) composite nanofibers in water is through cross-linking with glutaraldehyde (GA). In this regard, the aim of this research is to determine the effect of GA cross-linking on the morphology of PChK composite nanofibers. The composite nanofibers used are P8Ch2K2, P8Ch2K4, and P8Ch2K8. The solution used for cross-linking is an Acetone:GA:HCl solution with a ratio of 9:1:0.01 and a reaction time of ±4 hours. Nanofiber characterization was carried out using SEM and analyzed using ImageJ and Origin. It was found that GA cross-linked nanofibers had a larger average fiber diameter, namely with an average increase of 7.54% and more continuous fiber length, namely with an average length increase of 42.06%, compared to nanofibers without GA cross-linking.